Dependence in a national sample of Aboriginal and Torres Strait Islander daily smokers. (1st June 2015) - Thomas, David P; Panaretto, Kathryn S; Stevens, Matthew; Borland, Ron
Abstract: Objectives: To examine indicators of nicotine dependence in a national sample of Aboriginal and Torres Strait Islander daily smokers and their association with sustaining a quit attempt for at least 1 month, and to make comparisons with a national sample of Australian daily smokers. Design, setting and participants: The Talking About The Smokes project used a quota sampling design to recruit 1392 daily smokers from communities served by 34 Aboriginal community‐controlled health services and one community in the Torres Strait from April 2012 to October 2013. These were compared with 1010 daily smokers from the general Australian population surveyed by the International Tobacco Control Policy Evaluation Project from September 2011 to February 2012. Main outcome measures: Cigarettes per day (CPD), time to first cigarette, Heaviness of Smoking Index (HSI), other indicators of dependence, and whether smokers had ever sustained a quit attempt for at least 1 month. Results: There was little difference in the mean HSI scores for Aboriginal and Torres Strait Islander and other Australian daily smokers. A higher proportion of Aboriginal and Torres Strait Islander daily smokers smoked ≤ 10 CPD (40% v 33.4%), but more also smoked their first cigarette within 30 minutes of waking (75% v 64.6%). Lower proportions of Aboriginal and Torres Strait Islander smokers reported having strong urges to smoke at least several times a day (51% v 60.7%) or that it would be very hard to quit (39% v 47.9%). Most Aboriginal and Torres Strait Islander smokers reported experiencing difficulties during their most recent quit attempt. All indicators of dependence, except CPD and strong urges, were positively associated with not having made a sustained quit attempt. Reported difficulties during the most recent quit attempt were more strongly associated with being unable to sustain quit attempts than were traditional measures of dependence. Conclusion: Aboriginal and Torres Strait Islander smokers' experiences of past attempts to quit may be more useful than conventional indicators of nicotine dependence in understanding their dependence.